2010
DOI: 10.1002/cyto.a.20999
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell tracking with a reversing flow cytometer

Abstract: We have developed an instrument based on a flow cytometer platform that is capable of tracking individual, suspended cells over extended time periods. The instrument repeatedly moves in a capillary the same volume segment of fluid containing tens to hundreds of suspended cells through the focal point of a laser. Individual cells are then tracked based on the timing of when they cross the laser, and cell properties are measured as in a conventional flow cytometer. Because cells are repeatedly measured the singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The distribution of GFP formation was broad for E. coli cells including non‐producer and cells that produced significantly larger amounts than the average cells. Similar results were found in S. cerevisiae cultures [ 1 , 31 , 54 ] as well as that constitutive expression of GFP is highly temperature dependent leading to oscillations [ 153 ]. ART‐FCM was also a rapid method to test promoter strength, plasmid stability and culture variability [ 30 ] demonstrating that small genetic changes could result in large variations in product formation.…”
Section: Automated Real‐time Flow Cytometry For Bioreactor Process An...supporting
confidence: 84%
See 2 more Smart Citations
“…The distribution of GFP formation was broad for E. coli cells including non‐producer and cells that produced significantly larger amounts than the average cells. Similar results were found in S. cerevisiae cultures [ 1 , 31 , 54 ] as well as that constitutive expression of GFP is highly temperature dependent leading to oscillations [ 153 ]. ART‐FCM was also a rapid method to test promoter strength, plasmid stability and culture variability [ 30 ] demonstrating that small genetic changes could result in large variations in product formation.…”
Section: Automated Real‐time Flow Cytometry For Bioreactor Process An...supporting
confidence: 84%
“…The current state of single-cell analysis involving microfluidics has been reviewed [20,[163][164][165]. In this context novel highly efficient microfluidics based FCs [153,166,167], microfluidic FIA systems [168] and microfluidic fluorescence-activated droplet sorter [117,169] are emerging. As comparability with conventional FCM studies could be shown [165,170], these devices bear great future potential as ART-FCM on a chip.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main drawbacks of actual on-line FC is its inability to follow the history of given cells inside the population (which makes it difficult to experimentally validate the two hypotheses behind heterogeneity in bioprocesses evoked in Section 2). Some attempts have been made for the adaptation of a conventional FC for the following of certain cells by recirculation of the sheath fluid [81], but this kind of system is difficult to interface with a bioreactor. At this time, the most efficient way to monitor the dynamics of a single cell is by the use of time-lapse fluorescence [82].…”
Section: Flow Cytometry For On-line Bioprocess Monitoringmentioning
confidence: 99%